Satisfaction Levels, Opinions, and Experiences of Asian Faculty on Campus: Does Citizenship Status Make A Difference? - Boyer, Patricia G.; Woodhouse, Shawn; Han, Pi-Chi (Advances in Social Sciences Research Journal, 2015)
The increasing complexity and diversity of U.S. society has enhanced the challenge of accommodating the needs of immigrants. University campuses in the United States are also becoming increasingly diverse, yet we cannot assume that diversity of numbers equates with acceptance of and respect for differences. The purpose of this study was to determine if there are differences in the perceptions of the campus and academic environment of Asian faculty employed in U.S. higher education institutions. There were three groups of Asian faculty members studied (1) U.S. citizens; (2) citizens, foreign born; and (3) non citizens using NSOPF:99 self-reported database. The theoretical framework utilized for this study is Herzberg’s work on hygiene theory, which explains the differences between employee satisfaction and dissatisfaction, as well as workplace factors that cause satisfaction or dissatisfaction. Several Multiple Analysis of Variance (MANOVA) were conducted to determine if there were statistically significant differences among the three groups of faculty focusing on 17 satisfaction and 12 opinion variables. The overall findings of the study revealed that Asian faculty members were both “somewhat dissatisfied” and “disagreed” with the majority of opinion variables related to the campus and academic environment. The study concludes with implications for administrators who will support Asian faculty members employed at higher education institutions.